Functional and taxonomic responses of tropical moth communities to deforestation. Issue 2 (8th November 2021) - Correa‐Carmona, Yenny; Rougerie, Rodolphe; Arnal, Pierre; Ballesteros‐Mejia, Liliana; Beck, Jan; Dolédec, Sylvain; Ho, Chris; Kitching, Ian J.; Lavelle, Patrick; Le Clec'h, Solen; Lopez‐Vaamonde, Carlos; Martins, Marlúcia B.; et al.
Abstract: Global insect decline has recently become a cause for major concern, particularly in the tropics where the vast majority of species occurs. Deforestation is suggested as being a major driver of this decline, but how anthropogenic changes in landscape structure affect tropical insect communities has rarely been addressed. We sampled Saturniidae and Sphingidae moths on 27 farms located in Brazilian Amazonia (Pará state) and characterised by different deforestation histories. We used functional traits (forewing length, body mass, wing load, trophic niche breadth and resource use strategy), analysed by combining RLQ and null model analyses, to investigate the responses of their taxonomic and functional diversity to landscape change dynamics and current structure. We found that communities had a higher proportion of large and polyphagous species with low wing load in landscapes with low forest quality and relative cover and high land use turnover. This was mainly due to a significant response to deforestation by saturniids, whereas the more mobile sphingids showed no significant landscape‐related pattern. We also observed an overall increase of species richness and functional dispersion in landscapes that have been deforested for a long time when compared with more recent agricultural settlements. Our results highlight the complex way in which landscape structure and historical dynamics interact to shape Neotropical moth communities and that saturniid moths respond clearly to the structure of the surrounding landscape, confirming their potential use as an indicator group for environmental monitoring programmes. Abstract : Species diversity and functional dispersion of moth communities (Saturniidae and Sphingidae) both increase from recently deforested to older transformed Amazonian landscapes. Moth communities have a higher proportion of large and polyphagous species with low wing load in landscapes with low forest quality and relative cover and high land use turnover. Taxonomic diversity and functional structure of Saturniidae assemblages (capital‐breeders) are significantly linked to landscape transformation, while Sphingidae (income‐breeders) show no significant response to deforestation.